Effects of active vitamin D3 and parathyroid hormone on the serum osteocalcin in idiopathic hypoparathyroidism and pseudohypoparathyroidism. - Mizunashi, K; Furukawa, Y; Miura, R; Yumita, S; Sohn, H E; Yoshinaga, K (The Journal of Clinical Investigation, 1988)
Serum osteocalcin was measured in patients with idiopathic hypoparathyroidism or pseudohypoparathyroidism, before or during the treatment with active vitamin D3 (1,25(OH)2D3 or 1 alpha OHD3). Serum osteocalcin and plasma 1,25(OH)2D were decreased in 11 patients with idiopathic hypoparathyroidism before treatment (2.8 +/- 1.27 ng/ml, P less than 0.001 and 14.3 +/- 4.27 pg/ml, P less than 0.001, respectively). In 24 patients with idiopathic hypoparathyroidism during the treatment, serum osteocalcin and plasma 1,25(OH)2D were within the normal range (4.5 +/- 0.74 ng/ml and 25.7 +/- 5.69 pg/ml, respectively). In five patients with pseudohypoparathyroidism before treatment, plasma 1,25(OH)2D was decreased (15.6 +/- 10.6 pg/ml, P less than 0.001) but serum osteocalcin was normal (7.8 +/- 1.66 ng/ml). In nine patients with pseudohypoparathyroidism during the treatment with active vitamin D3, serum osteocalcin and plasma 1,25(OH)2D were normal (6.8 +/- 1.47 ng/ml and 27.2 +/- 6.0 pg/ml, respectively). Serum PTH in pseudohypoparathyroidism was increased before treatment (0.70 +/- 0.34 ng/ml, P less than 0.05) and was normal during the treatment (0.50 +/- 0.13 ng/ml). In idiopathic hypoparathyroidism, the active vitamin D3 increased serum osteocalcin without PTH. In pseudohypoparathyroidism, PTH may increase serum osteocalcin or modulate the effect of active vitamin D3 on serum osteocalcin.